Correlation of creatinine‐ and specific gravity‐normalized free and glucuronidated urine cannabinoid concentrations following smoked, vaporized, and oral cannabis in frequent and occasional cannabis users. Issue 7 (15th March 2019) - Huestis, Marilyn A.; Blount, Benjamin C.; Milan, Daniel F.; Newmeyer, Matthew N.; Schroeder, Jennifer; Smith, Michael L.
Abstract: Variability in urine dilution complicates urine cannabinoid test interpretation. Normalizing urine cannabinoid concentrations to specific gravity (SG) or creatinine was proposed to account for donors' hydration states. In this study, all urine voids were individually collected from eight frequent and eight occasional cannabis users for up to 85 hours after each received on separate occasions 50.6 mg Δ9‐tetrahydrocannabinol (THC) by smoking, vaporization, and oral ingestion in a randomized, within‐subject, double‐blind, double‐dummy, placebo‐controlled protocol. Each urine void was analyzed for 11 cannabinoids and phase I and II metabolites by liquid chromatography−tandem mass spectrometry (LC–MS/MS), SG, and creatinine. Normalized urine concentrations were log10 transformed to create normal distributions, and Pearson correlation coefficients determined the degree of association between the two normalization methods. Repeated‐measures linear regression determined if the degree of association differed by frequent or occasional cannabis use, or route of administration after adjusting for gender and time since dosing. Of 1880 urine samples examined, only 11‐nor‐9‐carboxy‐THC (THCCOOH), THCCOOH‐glucuronide, THC‐glucuronide, and 11‐nor‐9‐carboxy‐Δ9‐tetrahydrocannabivarin (THCVCOOH) were greater than the method's limits of quantification (LOQs). Associations between SG‐ and creatinine‐normalized concentrations exceeded 0.90. Repeated‐measures regression analysis found small but statistically significant differences in the degree of association between normalization methods for THCCOOH and THCCOOH‐glucuronide in frequent vs occasional smokers, and in THCVCOOH and THC‐glucuronide by route of administration. For the first time, SG‐ and creatinine‐normalized urine cannabinoid concentrations were evaluated in frequent and occasional cannabis users and following oral, smoked, and inhaled cannabis. Both normalization methods reduced variability, improving the interpretation of urine cannabinoid concentrations and methods were strongly correlated. Abstract : The correlation of specific gravity and creatinine normalized phase I and II urine cannabinoids following controlled administration of THC by oral, smoked, and vaporized routes of administration was strong despite being statistically influenced by gender and time since dosing. Pearson correlation coefficients are shown for the analytes with small differences in association by group (A) and route of administration (B).